Optimal economic dispatch of combined cooling, heating and power‐type multi‐microgrids considering interaction power among microgrids. Issue 3 (21st May 2019) - Xu, Qingshan; Li, Lin; Chen, Xi; Huang, Yu; Luan, Kaining; Yang, Bin
Abstract : With the rapid growth of microgrids, many regional multi‐microgrids systems emerge gradually with microgrids being integrated to the certain distribution network. By connecting each microgrid using cables and coordinating interaction power among microgrids, the total operation cost of multi‐microgrids system can be decreased. On the basis of modeling a variety of energy supply and storage devices, this paper proposes an energy supply infrastructure for combined cooling, heating and power (CCHP) microgrid on centralized and interconnected energy exchange network, and energy loads are subdivided into cooling load, thermal load and power load. Then the optimal economic dispatch model considering interaction power among microgrids is proposed in this study for CCHP type multi‐microgrids, and energy balance constraints are established according to load types. This model not only takes into account the power interaction between microgrid and the distribution network, but also considers the power interaction among microgrids. The objective is the minimal total operation cost of CCHP type multi‐microgrids system. In case studies of Sino‐Singapore district, Tianjin, China, the output power of pre‐defined equipment and the total operation cost are compared under two different operation mode, coordination mode and independence mode, which verifies the effectiveness and economy of the proposed model.